Molecular diagnostics : the key driver in personalized cancer medicine - Jørgensen, Jan Trøst; Winther, Henrik (Pan Stanford Pub., 2010)
Provides an overview of molecular cancer diagnostic assays, which are the prerequisites for optimal solutions within personalized cancer medicine. This book offers definitions of the pharmacodiagnostic concept, and historical perspectives of the early steps into molecular cancer diagnostics linked to therapy.